Impact and Relevance of Modern Technological Legal Educational Facilities amidst the Covid-19 Pandemic: A Case Study of Law Students of Edo University Iyamho - Aidonojie, Paul Atagamen; Anne, Odojor Oyenmwosa (NIU Journal of Humanities; Vol. 5 Núm. 4 (2020): KIU Journal of Humanities, Vol. 5 No. 4, December 2020, 2021)
The study investigates the impact and relevance of modern technological educational facilities/resources amidst the Covid-19 pandemic, using Edo University Iyamho undergraduate law students as a case study. We administered 65 online structured questionnaires to law students of Edo University Iyamho. We used a descriptive and analytical method for analyzing data generated from the questionnaire. The study found that Edo University Iyamho is well equipped with ICT educational facilities/resources in the training of law undergraduate students, and it has been very viable in conducting e-learning/research amidst the Covid-19 pandemic. The study also found that poor network and epileptic power supply are some significant challenges often encountered in utilising modern technological educational facilities/resources. Given this, it was concluded and recommended that Nigeria Government should invest more on electricity to ensure steady power supply, and internet network providers should ensure effective and efficient network. Keywords: Information Communication Technology, Covid-19, Education, Law Student, Edo University Iyamho